The common agricultural policy after 2013 - Jean-Christophe Bureau; Stefan Tangermann; Alan Matthews; Davide Viaggi; Christophe Crombez; Louise Knops; Johan Swinnen (Intereconomics, 2012)
In October 2011 the European Commission presented a set of legal proposals designed to make the Common Agricultural Policy more effective. Pending a debate in the European Parliament and the Council, approval is expected by the end of 2013. This Forum aims to identify the proposals' shortcomings and to offer suggestions for improvement which the Parliament and Council can work to implement. The authors pay particular attention to the future of direct payments, CAP greening and rural development, as well as to the change in the decision-making rules which grants the Parliament more authority over the process.
Keywords: 330; EU-Agrarpolitik; Agrarreform; Agrarsubvention; Landwirtschaftliche Entwicklung; EU-Staaten